2016
DOI: 10.14238/sp14.6.2013.369-73
|View full text |Cite
|
Sign up to set email alerts
|

Infeksi Gigi Sebagai Faktor Pencetus Terbanyak Henoch-Schonlein Purpura dengan Keterlibatan Ginjal

Abstract: Latar belakang.Henoch Schonlein purpura (HSP) dengan keterlibatan ginjal memiliki prognosis yang lebih buruk, dan infeksi gigi merupakan faktor risiko terbanyak terjadinya HSP dengan keterlibatan ginjal. Tujuan.Menganalisis hubungan antara riwayat infeksi gigi dan terjadinya HSP dengan keterlibatan ginjal pada anak.Metode.Penelitian retrospektif dengan rancangan potong lintang terhadap 146 anak yang didiagnosis HSP berdasarkan kriteria American College of Rheumatology(ACR) sertaEuropean League Against Rheumati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Research conducted at Hasan Sadikin Hospital (RSHS) Bandung stated that there was an increase in the incidence of HSP from 2008 to 2010, and most patients had odontogenic infections. 11,27 In line with research conducted by Igawa et al26 who reported that focal oral infections may be a precipitating factor for HSP. Research conducted by Abe et al 7 in their case report concluded that periodontal infection and apical periodontitis are the main candidate factors causing HSP in these patients, 7 therefore, it is very important to maintain comprehensive oral health in HSP patients.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Research conducted at Hasan Sadikin Hospital (RSHS) Bandung stated that there was an increase in the incidence of HSP from 2008 to 2010, and most patients had odontogenic infections. 11,27 In line with research conducted by Igawa et al26 who reported that focal oral infections may be a precipitating factor for HSP. Research conducted by Abe et al 7 in their case report concluded that periodontal infection and apical periodontitis are the main candidate factors causing HSP in these patients, 7 therefore, it is very important to maintain comprehensive oral health in HSP patients.…”
Section: Discussionsupporting
confidence: 73%
“…7 Ghrahani et al 11 in their research conducted at the Department of Pediatrics at Hasan Sadikin Hospital (RSHS) Bandung from 2006 to 2011 found that 13.3% of HSP cases were probably caused by odontogenic infections. Another study also conducted at RSHS Bandung in 2013 found that in 41 patients with HSP with kidney involvement, odontogenic infection was the most precipitating factor compared Advances in Health Sciences Research, volume 48 to other precipitating factors, as many as 25 patients, 27 this requires special attention because it can become a focus of infection. 11 All these data indicate that chronic infection that occurs in the oral cavity plays a role in the occurrence of the pathogenic process in HSP.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations